PENGARUH FUNDAMENTAL TERHADAP HARGA SAHAM SYARIAH PERUSAHAAN SEKTOR CONSUMER GOODS DI BURSA EFEK INDONESIA PERIODE 2016- 2020 - Wijaya, Tommy; Maharani, Yunita; Tri Setyo Mulyani, Hendarti (Jurnal Ilmiah Niaga Bisnis Elektronik, 2021)
This research was written by Tommy Wijaya, NIM 130170029 majoring in Accounting with the title "Fundamental Influence On The Prices Syariah Company Stock Sector Consumer Goods At The Indonesian Stock Exchange The Period 2016-2020". This research was entitled "Fundamental influence on the prices syariah company stock sector consumer goods at the indonesian stock exchange the period 2016-2020. This research used quantitative research methods and purposive sampling technique which used 5 companies as the sample of this study. The type of data used in this study is secondary data followed by data collection techniques using financial statements. Meanwhile, the data analysis techniques used in this study are descriptive statistics of variables, the classical assumption test, multiple linear regression, and hypothesis testing. The results of the study showed that the Stock Price Variable could be explained by the independent variables in Price to Book Value (PBV) research, Price Earning Ratio (PER) and Earning Per Share (EPS) as a big 50.1% while the remaining 49.9% was explained by the other variables that were not examined or were not included in this regression model. Meanwhile the Price to Book Value (PBV) (X1), Price Earning Ratio (PER) (X2) and Earning Per Share (EPS) (X3) simultaneously had a positive effect and significant effect to the Sharia Share Prices of Consumer Goods sector companies that are included in the Jakarta Islamic Index (JII). The results of the partial test (T test) show that the significance value of Price to Book Value (X1), (0.551) < (0.05) and Price Earning Ratio (X2), (0.863) < (0.05) which meant the Price to Book Value and Price Earning Ratio had no positive and significant effect on Sharia Stock Prices (Y), while Earning Per Share (X3), with a significant value (0.004) < (0.05) had a positive and significant effect to the Sharia Share Prices of Consumer Goods companies in the Jakarta Islamic Index (JII).